Smart bilayer polymer reactor with cascade/non-cascade switching catalyst characteristics. (September 2020) - Wei, W.; Xiao, P.; Thakur, V.K.; Chianella, I.; Li, S.
Abstract: In this work, a new method is proposed to meet the challenge of preparing new catalysts with cascade/non-cascade switching catalytic property. Inspired from "soft" characteristics and divisional isolation function in natural biological systems, this objective was accomplished by developing a new class of hydrogels made of two unique functional layers with different temperature responses where each may self-govern coupled processes at a specific temperature. This hydrogel polymer reactor exhibited almost no catalytic activity at low-temperature range (<37 °C) as both channels of bilayer hydrogel polymer catalyst were closed. At modest temperatures (between 37 °C and 50 °C), the first step of the tandem reaction (the hydrolysis of p-nitrophenyl acetate (NPA)) showed significant reactivity that arises from the relaxing of the weak polymer complexes in the hydrogel layer. This enabled NPA the access to the acidic catalytic active center of the hydrogel. At range of higher temperatures (>50 °C), the hydrogel catalytic polymer reactor further exhibited significant efficiency towards the hydrolysis reaction of NPA as well as the reduction of the intermediate product p-nitrophenol (NP). This mainly resulted from the opening of both the weak polymer complexes and the stronger polymer complexes hydrogel layers, allowing entrance to both the acidic catalytic active center and the metal nanoparticles active center. As a result, the novel hydrogel polymer reactor could be used to control cascade/non-cascade catalysis reactions. This new protocol enables efficient control of switchable tandem reactions, inspiring for difficulty to control tandem catalytic reactors. Graphical abstract: Image 1 Highlights: Facile synthesis of smart bilayer polymer reactor. Excellent cascade and non-cascade switching catalyst properties. Detailed electrochemical and structural characterisation.